UNDERSTANDING MILLENNIALS INVESTMENT BEHAVIOR IN PEER-TO-PEER LENDING: CASE STUDY FROM INDONESIA - Natalia Natalia; Matthew Matthew (International Journal of Organizational Business Excellence, 2020)
Peer-to-Peer (P2P) Lending has become alternative investment option that expected to experience tremendous growth with the evolvement of technology solutions as people become more and more digitally connected. Millennials becomes the most interesting target generations for P2P Lending platform as this generations highly exposed by digital technology. Due to different characteristics and behavior of millennials dealing with financial and investment products, the research aims to distinguish these characteristics and behaviors and group them into several groups. The purpose of this research is to study Millennials investment behavior in P2P Lending platform based on demography, financial behavior and marketing media preference. Online survey was conducted to 205 respondentsin Indonesia who have understand or have invested in Peer to Peer Lending platform. Cluster Analysis is to analyze the data and categorized given sample into several groups who have similar characteristics and behavior. The results show 4 distinctive segments, they are Budding Millennial Investors, Confident Millennial Investors, Financially Oblivious Millennials and Pragmatic White-Collar Millennial Investors. By distinguishing distinctive groups within given population, can provide better understanding towards millennials investment behavior in P2P lending platform and therefore can help marketing managers and decision maker to develop better marketing strategy in targeting millennials investor.